Improving the quality of patient service to reduce medical errors: A narrative review - Alshammari, Fawaz Awdah Mohammad; Alshammari, Hassan Mohammed Brahim (International journal of health sciences, 2018)
Medical errors occur worldwide. Lifestyle diseases are on the rise in developing countries like India, and with increased changes in lifestyle, the number of patient-doctor interactions will escalate. Hence, they should be armed with information on how to decrease the number of medical errors by increasing the provision of patient services. Profound factors leading to improved patient care include enhancing empathic and compassionate communication, improving electronic health records, embedding virtual reality to enhance patient engagement, drawing up guidelines for increasing patient understanding, and increasing physician responsibilities in patient management. We conclude that healthcare organizations need to start seeing patient care as a business and increase their investment in technology and human resources. Continuous education and audit of physicians should also be encouraged. There is also a need for collaborative research with healthcare organizations on how technology can be expanded. Policies and guidelines can also be drawn to teach these tips to clinician educators.